2011
DOI: 10.1093/cvr/cvr232
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in adult Alk1 heterozygous mice due to oxidative stress

Abstract: The increased pulmonary vascular remodelling in Alk1(+/-) mice leads to signs of PH and is associated with eNOS-dependent ROS production, which is preventable by anti-oxidant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 37 publications
2
59
0
Order By: Relevance
“…BMP4 treatment of mouse aortaes led to impaired endothelium-dependent relaxations, exaggerated endothelium-dependent contractions via cyclooxygenase-2 (COX-2) upregulation in a reactive oxygen species (ROS) dependent manner [129]. It has been also reported that increased pulmonary vascular remodelling in Alk1+/− mice leads to signs of PAH and it has been shown that this is associated with eNOS-dependent ROS production and it can be averted by anti-oxidant treatment [130]. Interestingly prostacyclin analogues were shown to enhance BMP induced Smad1/5 phosphorylation by suppressing Smad6 expression [131].…”
Section: Vascular Tone and Tgf Signalingmentioning
confidence: 99%
“…BMP4 treatment of mouse aortaes led to impaired endothelium-dependent relaxations, exaggerated endothelium-dependent contractions via cyclooxygenase-2 (COX-2) upregulation in a reactive oxygen species (ROS) dependent manner [129]. It has been also reported that increased pulmonary vascular remodelling in Alk1+/− mice leads to signs of PAH and it has been shown that this is associated with eNOS-dependent ROS production and it can be averted by anti-oxidant treatment [130]. Interestingly prostacyclin analogues were shown to enhance BMP induced Smad1/5 phosphorylation by suppressing Smad6 expression [131].…”
Section: Vascular Tone and Tgf Signalingmentioning
confidence: 99%
“…ROS may be involved in development of HPV and pulmonary hypertension due to diverse mechanisms, either by the above mentioned disruption in the NO-pathway, by interaction with the endothelial layer, or by uncoupling of oxidases, such as xanthine oxidase and nicotinamide adenine dinucleotide phosphate oxidase (Demarco et al, 2010 ;Jerkic et al, 2011 ;Lane et al, 2011). Because of their short half lives, quantification of ROS is difficult and requires special methodological settings.…”
Section: Oxidative Stress In Hypobaric Hypoxia and Influence On Vessementioning
confidence: 99%
“…Mice with a heterozygous deletion of Alk1 have been found to develop PH associated with increased ROS production. The level of NO production is decreased, partially because of decreased production caused by eNOS uncoupling and partially because of a ROS-mediated reduction in NO bioavailability (53).…”
Section: Edno As a Paracrine Regulatormentioning
confidence: 99%
“…Such action is diminished in pulmonary hypertension, in part because of reduced production of NO by uncoupled endothelial nitric oxide synthase (eNOS) (34). The uncoupled eNOS generates superoxide anions, which reduce the bioavailability of NO (53). NO can counteract the vasoconstriction and vascular remodeling caused by ET-1 action through the stimulation of soluble guanylyl cyclase (sGC) and the elevation of cyclic guanosine monophosphate (cGMP).…”
Section: Edno As a Paracrine Regulatormentioning
confidence: 99%